Maternal Healthcare Interventions Implemented Amid the COVID-19 Pandemic in Mmabatho, North-West, South Africa - Mohulatsi , Makgake Ziphorah; Garutsa, Tendayi Clotilda; Bahule, Boipelo Judith (Journal of Ecohumanism, 2025)
South Africa has made substantial investments in enhancing maternal and neonatal health services; nevertheless, the country fell short of achieving the Millennium Development Goals (MDGs) for maternal and child health by 2015. Despite having established national maternal and neonatal health policies and objectives, the absence of a unified quality improvement approach poses challenges. The impact of the COVID-19 epidemic has further complicated these difficulties, creating obstacles to healthcare access and hindering the implementation of maternal and perinatal interventions. The purpose of the study was to explore the interventions implemented in maternal healthcare in Mmabatho, North-West, South Africa, amidst the challenges posed by the COVID-19 pandemic. The study employed a qualitative research design, specifically utilizing key informant interviews as the primary method of data collection. The findings underscore the pivotal role played by community-based interventions, particularly the involvement of community health workers, in providing information and support for maternal healthcare. Although awareness of digital health programs varied among participants, they were commended for disseminating knowledge about maternal healthcare. Recommendations include the development of mHealth initiatives, the expansion of community-based interventions, the involvement of males in maternal healthcare, and the implementation of monitoring and evaluation systems should be considered to assess the efficacy of interventions.